Cyclopentadithiophene based branched polymer electrets synthesized by friedel–crafts polymerization. Issue 19 (5th July 2016) - Liu, Zhengdong; Bao, Yan; Ling, Haifeng; Hu, Hui; Ju, Hao; Xie, Linghai; Bian, Linyi; Chang, Yongzheng; Yi, Mingdong; Huang, Wei
ABSTRACT: In this report, the BF3 ·Et2 O catalyzed Friedel–Crafts polymerization of cyclopentadithiophene monomers for branched conjugation‐interrupted polymer electrets with the potential application in OFET memories were demonstrated. Branched polycyclopentadithiophenes with controlled molecular weights ( M n ) of approximately 8800 g/mol and narrow polydispersity index (PDI = 1.08–1.49) were obtained through the optimized polymerization temperature and time, and monomer addition strategy. OFET memories by using the synthesized polymers as the electret layers were fabricated and exhibited multilevel flash memory behaviors, wide memory windows, high on/off ratios, and long retention lifetime. Impressively, due to the strong hydrophobic, extended pi‐conjugation and electron‐donating properties, the branched polycyclopentadithiophene based OFET memory exhibited much lower programming voltage than other branched polymer electrets based devices. It is expected that the branched polycyclopentadithiophenes probably have potential application in other organic electronic devices. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3140–3150 Abstract : Branched polycyclopentadithiophenes with controlled molecular weights and narrow polydispersity index were synthesized by BF3 ·Et2 O catalysed Friedel–Crafts polymerization. After that, OFET memories were prepared by using branched polycyclopentadithiophenes as the electret layers. These devices show wide memory windows, high on/off ratios and long retention lifetime. The effects of the substituent groups (alkyl and alkoxyl chains) on the properties of the polymers and the performances of these devices were further discussed.